Genetic Characterization of Aspergillus flavus and Saccharomyces cerevisae in Tracheobronchial Phlegm of HIV-infected Patients on Antiretroviral Therapy in Jalingo, Nigeria (Bangladesh Medical Journal, 2024)
Fungal infections are among the diverse respiratory tract pathogens and account for a proportion of community acquired and nosocomial pneumonias thereby generating concerns particularly in immunocompromised patients. This study aims to genomically extract and sequence fungal DNA using the Basic Local Alignment Search Tool (BLAST) technology for their definitive and confirmatory identification thereby easing off the obstacles in their diagnosis due to similar appearance in their colony and morphology and ultimately determining their infection rates in persons receiving antiretoviral therapy against HIV. Sputa of 100 HIV infected out-patients of a Medical Centre in Jalingo, on anti-retroviral therapy were cultured on Sabouraud Dextrose Agar to isolate fungi species and assess their prevalence and distribution. Fungal colonies characterized culturally and biochemically as Aspergillus flavus and Aspergillus niger were subjected to the BLAST, and the similarities with the biological sequences in the National Center for Biotechnology Information (NCBI) database queried. There were observational variances in the colonial and microscopic appearances of A. flavus and A. niger on Sabouraud Dextrose Agar (SDA) plates and the microscope respectively. The similarities between the queried and biological sequences in the NCBI database, was almost all (99.7%) thus confirming their identity as Aspergillus flavus and Saccharomyces cerevisiae. The overall prevalence of fungi infection was 79.0%. More males (80.0%) than females (78.3%) were infected. In both sexes, fungi were most (92.9%) frequently isolated in patients that were between 30 and 39 years and least (64.7%) in those between 15 and 29 years. There was no established pattern (sex- and age- relatedness) of non-concomitant A. flavus and S. cerevisiae in fifty-seven male and female patients in six age categories even though A. flavus occurred more (48.1%) than S. cerevisae (24.1%) and the prevalence was higher (61.4%) in females than in males (38.6%). The high prevalence of these fungi in the study population, with or without symptoms of cough or fungal disease, mandates an early screening of such infected persons so as to reduce further complications and improve treatment.Bangladesh Med J. 2023 Jan; 52(1): 6-11